Hasan al-Turabi’s Methodology in al-Tafsīr al-Tawḥīdī: A Contextual and Ideological Approach to Qur’anic Interpretation - Safa, Abdillah; Maram, Ahmad Nabilul; Wara, Jullul; Ahmadi, Ahmadi (QOF, 2025)
This study examines the exegetical methodology of Hasan al-Turabi in al-Tafsīr al-Tawḥīdī, a work distinguished by its tawḥīdī (unificationist) and ḥarakī (activist) framework. Using content analysis and ideological critique, this study dissects its epistemological foundations and interpretive strategies. The findings reveal several key characteristics. First, the concept of tawḥīd is not merely interpreted theologically but is operationalized as an epistemological principle and methodological foundation for a socio-political reform project. Second, his method selectively combines traditional sources (tafsīr bi al-riwāyah) with a dominant rational reasoning (tafsīr bi al-dirāyah), aligning with his ideological framework. Third, its structure employs a tahlīlī (analytical-sequential) method yet with a strong thematic touch through its tripartite systematics: a preface (khulāṣah hadī al-sūrah), a structural summary (tartīl al-ma‘ānī), and a detailed contemporary analysis (‘umūm al-ma‘ānī). Fourth, its interpretive flow is analytic-inductive, moving from a holistic overview of the sūrah to specific meanings, thereby building an action-oriented systemic paradigm. However, the analysis also reveals several fundamental weaknesses. A heavy reliance on ra'y, while sidelining the corpus of Hadith, creates space for the instrumentalization of the text for ideological purposes. Furthermore, his work is criticized for its limited methodological originality and inconsistent application of his method, suggesting a potential selective bias. This study offers a structured methodological assessment, sharply highlighting the dynamics and limitations of the tafsīr ḥarakī genre within contemporary Islamic discourse.